Toxicology and carcinogenesis studies of 1-bromopropane (CAS No. 106-94-5) in F344/N rats and B6C3F1 mice (inhalation studies) - National Toxicology Program (National Toxicology Program technical report series, 2011)
In the early to mid 1990s, 1-bromopropane was used primarily as an intermediate in the production of pesticides, quaternary ammonium compounds, flavors and fragrances, pharmaceuticals, and other chemicals in well-controlled, closed processes. In the mid to late 1990s, it was introduced as a less toxic replacement for methylene chloride in emissive applications such as vapor and immersion degreasing operations and critical cleaning of electronics and metals. 1-Bromopropane was also introduced as a nonflammable, nontoxic, fast-drying, and inexpensive solvent for adhesive resins, and has been marketed as a replacement for ozone depleting refrigerants. 1-Bromopropane was nominated for study by the Occupational Safety and Health Administration based on the potential for widespread occupational and environmental exposure and a lack of toxicity and carcinogenicity data. Male and female F344/N rats and B6C3F1 mice were exposed to 1-bromopropane (99% or greater pure) by inhalation for 2 weeks, 3 months, or 2 years. Genetic toxicology studies were conducted in Salmonella typhimurium and Escherichia coli and mouse peripheral blood. 2-WEEK STUDY IN RATS: Groups of five male and five female rats were exposed to 1-bromopropane vapor at concentrations of 0, 125, 250, 500, 1,000, or 2,000 ppm, 6 hours plus T90 (12 minutes) per day, 5 days per week for 16 days. All rats survived to the end of the study except one 500 ppm male. Mean body weights of 2,000 ppm rats were significantly less than those of the chamber controls. The absolute kidney weight of 1,000 ppm males, relative kidney weights of all exposed groups of males, and absolute and relative kidney weights of all exposed groups of females were significantly increased. The absolute and relative liver weights of 1,000 ppm males, relative liver weights of 500 and 2,000 ppm males, and absolute and relative liver weights of 500 ppm or greater females were significantly increased. Nasal lesions included suppurative inflammation in males exposed to 500 ppm or greater, respiratory epithelial necrosis in 1,000 and 2,000 ppm males, and respiratory epithelial regeneration in 1,000 and 2,000 ppm females. 2-WEEK STUDY IN MICE: Groups of five male and five female mice were exposed to 1-bromopropane vapor at concentrations of 0, 125, 250, 500, 1,000, or 2,000 ppm, 6 hours plus T90 (12 minutes) per day, 5 days per week for 17 days. All 2,000 ppm males, two 2,000 ppm females, four 500 ppm males, one 1,000 ppm male, and one 1,000 ppm female died early. The mean body weight gain of 1,000 ppm males was significantly less than that of the chamber controls. Abnormal breathing, lethargy, and eye discharge were observed primarily during week 1 in groups exposed to 500 ppm or greater. Liver weights of 1,000 ppm males and of females exposed to 500 ppm or greater were significantly increased. Kidney weights of 1,000 and 2,000 ppm females were significantly increased. Microscopic lesions related to 1-bromopropane exposure occurred in the lung, liver, and nose of males and females and were primarily seen in mice exposed to 500 ppm or greater. 3-MONTH STUDY IN RATS: Groups of 10 male and 10 female rats were exposed to 1-bromopropane vapor at concentrations of 0, 62.5, 125, 250, 500, or 1,000 ppm, 6 hours plus T90 (10 minutes) per day, 5 days per week for 14 weeks. Additional clinical pathology groups of 10 male and 10 female rats were exposed to the same concentrations for 23 days. All rats survived to the end of the study. Mean body weights of 1,000 ppm males were significantly less than those of the chamber controls. The increases in sorbitol dehydrogenase activities in 500 ppm males and 1,000 ppm males and females were consistent with the histopathologic evidence of mild hepatotoxicity caused by 1-bromopropane. Liver weights of males exposed to 250 ppm or greater and of females exposed to 125 ppm or greater were significantly increased. Spleen and kidney weights of 1,000 ppm females were significantly increased. Exposure concentration-related decreases of 28% in sperm motility and 37% in sperm counts were seen in the 1,000 ppm group of male rats. Female rats in all three exposure groups evaluated exhibited altered estrous cycles, spending significantly more time in extended estrus and less time in extended diestrus. The incidences of cytoplasmic vacuolization of the liver were significantly increased in males exposed to 250 ppm or greater and in females exposed to 500 ppm or greater. Hepatocyte degeneration was also observed in 1,000 ppm females. 3-MONTH STUDY IN MICE: Groups of 10 male and 10 female mice were exposed to 1-bromopropane vapor at concentrations of 0, 62.5, 125, 250, or 500 ppm, 6 hours plus T90 (10 minutes) per day, 5 days per week for 14 weeks. One 250 ppm male and four males and five females in the 500 ppm groups died early. Mean body weights of exposed groups were similar to those of the chamber controls. Lethargy was observed in males and females exposed to 500 ppm, and abnormal breathing was observed in moribund mice. The kidney, liver, and lung weights of 500 ppm females were significantly greater than those of the chamber controls. The kidney weights of 500 ppm males were significantly decreased. Sperm counts in the 500 ppm group of male mice were 28% less than that in the chamber controls. Female mice exhibited altered estrous cycles, with females in the 500 ppm group spending significantly more time in extended diestrus and those in the 250 ppm group spending significantly more time in extended estrus compared to the chamber controls. Nonneoplastic lesions were observed in the nose, larynx, trachea, lung, and liver of 500 ppm males and females and in the adrenal cortex of 500 ppm females. 2-YEAR STUDY IN RATS: Groups of 50 male and 50 female rats were exposed to 1-bromopropane vapor at concentrations of 0, 125, 250, or 500 ppm, 6 hours plus T90 (10 minutes) per day, 5 days per week for 105 weeks. Survival of 500 ppm males was significantly less than that of the chamber control group. Mean body weights of exposed groups were similar to those of the chamber controls. Increased incidences of macroscopic, soft, pale-yellow to green, variably sized nodules were seen predominantly in the nose and skin of exposed rats. The number of animals with multiple masses was increased in the 500 ppm groups. In most cases, these lesions were microscopically shown to be suppurative inflammation, many with Splendore-Hoeppli material. The incidence of adenoma of the large intestine (colon or rectum) was significantly greater in 500 ppm females than in the chamber control group. The incidence of adenoma of the large intestine in 250 ppm males exceeded the historical control ranges for inhalation studies and all routes. The incidences of keratoacanthoma, basal cell adenoma, basal cell carcinoma, or squamous cell carcinoma (combined) were significantly greater in all exposed groups of males than in the chamber control group and exceeded the historical control range for inhalation studies. The incidences of keratoacanthoma and of keratoacanthoma or squamous cell carcinoma (combined) in 250 and 500 ppm males were also significantly increased and exceeded the historical control ranges for inhalation studies. In 500 ppm females, the incidence of squamous cell papilloma, keratoacanthoma, basal cell adenoma, or basal cell carcinoma (combined) exceeded the historical control range for inhalation studies. The incidence of malignant mesothelioma was significantly greater in 500 ppm males than in the chamber control group. The incidences of pancreatic islet adenoma in all exposed groups of males and of pancreatic islet adenoma or carcinoma (combined) in 125 and 250 ppm males were significantly increased. Treatment-related nonneoplastic lesions were observed in the respiratory system of exposed male and female rats. In the nose, the incidences of suppurative chronic inflammation, chronic active inflammation, glandular hyperplasia, respiratory epithelial hyperplasia (females), and respiratory metaplasia of the olfactory epithelium (females) were increased in all exposed groups. In the larynx, the incidences of chronic active inflammation and squamous metaplasia (except 125 ppm females) were increased in all exposed groups, and the incidences of suppurative chronic inflammation were increased in the 500 ppm groups. Also, chronic inflammation of the lung was observed in the 500 ppm females. In the trachea, there were increased incidences of chronic active inflammation in all exposed groups of females and 500 ppm males, and the incidence of epithelial hyperplasia was increased in 500 ppm females. 2-YEAR STUDY IN MICE: Groups of 50 male and 50 female mice were exposed to 1-bromopropane vapor at concentrations of 0, 62.5, 125, or 250 ppm, 6 hours plus T90 (10 minutes) per day, 5 days per week for 105 weeks. Survival of exposed groups was similar to that of the chamber controls. Mean body weights of all exposed groups were similar to...